Startling stimuli increase maximal motor unit discharge rate and rate of force development in humans - Škarabot, Jakob; Folland, Jonathan P.; Holobar, Aleš; Baker, Stuart N.; Del Vecchio, Alessandro (Journal of Neurophysiology, 2022)
Maximal rate of force development in adult humans is determined by the maximal motor unit discharge rate, however, the origin of the underlying synaptic inputs remains unclear. Here, we tested a hypothesis that the maximal motor unit discharge rate will increase in response to a startling cue, a stimulus that purportedly activates the pontomedullary reticular formation neurons that make mono- and disynaptic connections to motoneurons via fast-conducting axons. Twenty-two men were required to produce isometric knee extensor forces "as fast and as hard" as possible from rest to 75% of maximal voluntary force, in response to visual (VC), visual-auditory (VAC; 80 dB), or visual-startling cue (VSC; 110 dB). Motoneuron activity was estimated via decomposition of high-density surface electromyogram recordings over the vastus lateralis and medialis muscles. Reaction time was significantly shorter in response to VSC compared with VAC and VC. The VSC further elicited faster neuromechanical responses including a greater number of discharges per motor unit per second and greater maximal rate of force development, with no differences between VAC and VC. We provide evidence, for the first time, that the synaptic input to motoneurons increases in response to a startling cue, suggesting a contribution of subcortical pathways to maximal motoneuron output in humans.NEW & NOTEWORTHY Motor unit discharge characteristics are a key determinant of rate of force development in humans, but the neural substrate(s) underpinning such output remains unknown. Using decomposition of high-density electromyogram, we show greater number of discharges per motor unit per second and greater rate of force development after a startling auditory stimulus. These observations suggest a possible subcortical contribution to maximal in vivo motor unit discharge rate in adult humans.
CRIS-Team Scopus Importer:2022-09-09
Keywords: ballistic contractions; EMG decomposition; motoneuron; reticular formation; StartReact